Optimalisasi Pakan Ternak Melalui Pembuatan UMMB di Desa Mekar Sari, Binuang, Kabupaten Tapin: Optimization of Animal Feed Through the Production of UMMB in Mekar Sari Village, Binuang, Tapin Regency - Dewi, Sarmilawati; Bumantara, Aldama; Hasanah, Ceria Mutiara; Meryam, Maya; Ariyanda, Yuda; Rizqiana, Sista (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This community service program focused on improving the quality of livestock feed by teaching people how to make Urea Molasses Multi-Nutrient Blocks (UMMB). The work took place in Mekar Sari Village, Binuang District, Tapin Regency, and involved the local community. The method used was Participatory Action Research (PAR), which means farmers were involved in planning, doing, and reviewing the project. They learned about making balanced feed, the advantages of using UMMB, and practiced making it with locally available materials. The participants were very excited and actively participated in both talking and activities. The UMMB they made looked good; it was dark brown, smelled sweet like molasses, was hard and uniform in texture, and didn't have any mold. This program helped farmers learn to make better feed, enabling them to cope with a lack of grass during dry seasons, save money on feed, and keep their animals healthier and more productive.